Laparoscopic management of rapunzel syndrome - Jayanth Bannur Nagaraja; Shashank Saraf; Nairuthya Shivathirthan; S Srinath (Apollo Medicine)
Rapunzel syndrome is caused by ingestion of hairs, which leads to formation of trichobezoar, which can extend up to small intestine especially in girls. Utility of laparoscopic approach for this condition is not well established in this population. We are presenting a case of Rapunzel syndrome in a 14-year-old girl presenting as a cause of gastric outlet obstruction. Early diagnosis and extraction of trichobezoar by laparoscopic-assisted approach in children may be a better approach with respect to cosmesis, lesser morbidity, and early recovery.